MANAJEMEN RISIKO DALAM RANTAI PASOK GLOBAL PADA MASA PANDEMI: STUDI KASUS EKSPOR PRODUK UMKM DI INDONESIA - Dina Sari; Harahap, Nurhamidah; Yasmin Sasmita; Sitepu, Salma Agita; Arsyadona Arsyadona (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze risk management strategies in the global supply chain during the pandemic, with a particular focus on the export of Micro, Small, and Medium Enterprises (MSME) products in Indonesia. The COVID-19 pandemic has significantly disrupted global supply chains, exposing vulnerabilities and highlighting the critical need for robust risk management. This research employs a qualitative method with a literature study approach, drawing insights from academic journals and books. Data is collected by synthesizing existing literature on supply chain risk management, global logistics, the impact of the pandemic, and the challenges faced by MSME exports. The findings indicate that effective risk management in global supply chains, especially for MSMEs, requires proactive strategies such as supplier and market diversification, adoption of digital technologies, and enhanced stakeholder collaboration. In conclusion, building a resilient and adaptive supply chain is essential for the sustainability of MSME exports in a volatile global environment, suggesting further research on policy support and the adoption of context-specific technologies in Indonesia.